Implementasi Sistem Invetori Hotel Marcopolo - Lusia Septia Eka Esti Rahayu; Sintong Prima Sinaga (Universitas Bandar Lampung (UBL), 2017)
Inventory information system is a system that is used to enter data into the inventory database, the error does not occur in the input, the output data and the creation of reports based on the data that you want. At Marcopolo Hotels Bandar Lampung, obtained information that the existing systems in the warehouses of Marcopolo Hotels still manual. Therefore, the system will be made by the author are the result of observation of the system that already exists in the warehouse Marcopolo Hotels Bandar Lampung. On information systems also include the features of reporting data, input, and output of goods, and the goods data search based on the name of the goods. By implementing this system at the warehouse Marcopolo Hotel, Bandar Lampung.Then it can reduce errors that often occur. This system is also more accelerate the process of input, output, and the making of the report helps shed part of the Marcopolo Hotels Bandar Lampung.